Persepsi Istri Terhadap Penggunaan Alat Kontrasepsi IUD Di Kabupaten Klaten - Astuti , Yuli (2012)
IUD contraception is one of the most effective contraceptives. based on the initial survey, IUD contraceptive users in the Klaten Regency still low. This study aims to determine the wife perception the IUD contraceptive use in Klaten Regency. The methods used a descriptiv research design with qualitative approach. The population in this study was the wife who use contraceptives than IUD many as 287 people. The obtainable of sample was 30 respondent. 15 respondent (50%) did not use IUD because they felt afraid of bleeding accident, 3 respondent (10%) felt uncomfortable in sex activity, 5 respondent (17%) felt embarrassed, and 4 respondent (13%) argue that the IUD is expensive. Beside, there are 3 respondent (10%) did know there reason why they did know use IUD.